The Araceae of Indomalaya I: Piptospatha N.E.Br. - Boyce, P.C; Wong Sin, Yeng (International Aroid Society, Inc., 2012)
A review of the genus Piptospatha N.E.Br. is presented with new generic boundaries implemented since the last full revision. 10 species are recognized, two of them (P. marginata (Engl.) N.E.Br. & P. repens H.Okada & Tsukaya) recognized only recently as distinct species. Two species (P. angustifolia Engl. ex Alderw. and P. remiformis Ridl.) are treated as inadequately known. A key to accepted species is given, and all species are illustrated, the majority from living plants